SOSIALISASI DAN EDUKASI RABIES DALAM PROGRAM KKN DI DESA CAMPLONG II KECAMATAN FATULEU KABUPATEN KUPANG - Nitbani, Heny; Selan, Yulfia Nelymalik; Saputra, Agus; Ndaong, Nemay Anggadewi; Laut, Meity Marviana; Maha, Inggrid Trinidad (Universitas Nusa Cendana, 2025)
Rabies is a fatal zoonotic disease and is still a threat to public health, especially in areas with high populations of disease-carrying animals. In 2024, there was a case of rabies in Sillu village, one of the villages in Kupang Regency. This village area is adjacent to Camplong II village, which is the locus of the Undana Veterinary Study Program KKN. Camplong II village is a strategic location for implementing rabies socialization and education programs. This activity aimed to increase public knowledge and awareness, especially among school children, regarding the dangers of rabies, prevention, and initial handling of bites from rabies-transmitting animals (HPR). The methods used were pre-test, socialization and education, distribution of pamphlets, interactive discussions, and post-tests. The evaluation results showed an 82% increase in children's understanding of rabies after the activity took place. This program shows that the right socialization and education approach can increase public awareness in efforts to prevent rabies.